Pengaruh Lingkungan Kerja dan Stres Kerja terhadap Kinerja Karyawan Pada PT Cakra Transport Utama - Fia Rosariya Rohmatun; Julinta Paulina; Arif Riyanto (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This study aims to determine whether there is effect from the work environment and work stress partially and simultaneously on employee performance at PT Cakra Transport Utama. This study uses primary data by distributing questionnaires to employees. The population used in this study were 60 people. The sample used is Proportionate Random Sampling and obtained 52 people as respondents. This study used statistical tests and used several data analysis techniques, namely descriptive analysis, simple and multiple linear regression tests, correlation and determination coefficient tests, and hypothesis testing. Based on the research test simultaneously the results of the analysis of variables (XI) Work Environment, (X2) Work Stress and (Y) Performance seen from the fcount of 15.069 with a ftable of 3.187 or 15.069 > 3.187 and the resulting significant value is 0.000 <0.05. It can be stated that the variables of Work Environment and Work Stress have an effect on Employee Performance at PT Cakra Transport Utama. And based on the results of the analysis of the coefficient of determination, the R Square value is 0.381 or 38.1%. So it can be concluded that the work environment and work stress together have an effect of 38.1% on employee performance, while the remaining 69.1% is influenced by other factors not examined in this study.